THE ANALYSIS OF INTERNAL CONTROL SYSTEMS EFFECTIVENESS IN RECEIPT OF CASH AT PT. MANDALA MULTIFINANCE, TBK BRANCH SIAU - Sabaru, Novianty Trisye; Elim, Inggriani (Universitas Sam Ratulangi, 2015)
The development of the business world is rapidly increasing, are experienced by companies engaged in leasing services. PT. Mandala Multifinance, Tbk Branch Siau, engaged in financing services of two-wheeled vehicles. In the competition the current management is aware of the importance of the unity of the company to be able to survive in the competition. Management is required to maintain the property, prevent the occurrence of errors and embezzlement. The cycle cach is most receipts vulnerable to realize cash proceeds of fraud, hence the importance of internal control procedures for cash receipts in order to avoid the problems that will occur. This study is aimed to evaluate the effectiveness of the internal control system of cash receipts cycle at PT. Mandala Multifinance, Tbk Branch Siau. The method used is descriptive qualitative method. The results shows the internal control system of the cash receipts at PT. Mandala Multifinance, Tbk Branch adequate Siau characterized by the elements of internal control has been executed and is effective. Management should do some improvements such as the organizational structure that needs to be reviewed, to support the effectivenessÂ Â of the existing internal control.Keywords: internal control, fraud, cash receipts.